Silver(I) complexes as model catalysts in olefin hydroformylation - Venter, Gertruida Jacoba Susanna (University of the Free State, 2007)
The aim of this study was to synthesize Ag(I) complexes of the type [AgXLn] (L = tertiary phosphine; n = 1-4; X = coordinating or non-coordinating anion) and explore the olefin hydroformylation activity and ligand exchange rates of these complexes. Tertiary phosphine complexes of Ag(I) of the type [AgXLn] (L = P(p-tol)3; n = 1-4; X = Br-, ClO4 -, PF6 -) were synthesized and characterized through X-ray crystallography. Selected crystal data is shown in Table 1. Table 1 Selected crystal data as obtained for the three Ag(I) crystal structures solved in this study. These complexes are comparable to similar complexes containing transition metals, other phosphine ligands or different counterions. Occurrences of similar structures in literature, however, were limited, indicating a field open to study. The behavior of Ag/PX3 complexes in solution are not yet explored, due to, amongst others, rapid and complex kinetics, and could be expanded on in future. The coordination of CO to these complexes for application as hydroformylation catalysts were investigated through high-pressure infrared spectroscopy. No evidence could be obtained through high-pressure infrared of coordination of CO to Ag(I) complexes. The aversion of the silver molecule to coordinate the CO molecule could be attributed to the coordination of bulky phosphine ligands, which could prevent the coordination of CO ligand to the metal centre, as well as the absence of a strong electron-accepting ligand, for example boron- or nitrogen-containing ligands. Another explanation is the high electron density surrounding the silver atom, which prevents -back bonding from the silver atom to the CO molecule. Kinetics of the exchange rate between coordinated phosphine ligands in these complexes and free phosphine is important, as this exchange rate could have an influence on the coordination of other ligands on the silver atom. The exchange rate was investigated using a NMR technique called magnetic spin transfer, or spin saturation transfer. In this method, the sample is saturated at a specific frequency, and through the relaxation of the peak at that frequency the exchange between free and coordinated phosphine could be established. The sample was investigated for different concentrations, shown in Table 2 with the calculated values of the rate of exchange. a) No e.s.d.’s were obtained from the fitting program, but are estimated to be ca. 10%. The rate of exchange at different concentrations is shown in Figure 1.The observed rate of exchange of free phosphine with coordinated phosphine is fast, in ca. 7 s-1 at -80 °C, with an average value of 29±60 mM-1.s-1 for k1 and 6.9±0.7 s-1 for k-1. The rate of exchange between coordinated and free phosphine has been found to be independent of the concentration of phosphine, indicating a dissociative mechanism. Since no evidence could be obtained of coordination of CO to the metal centre, application of complexes of Ag(I) of the type [AgXLn] (L = tertiary phosphine; n = 1-4; X = coordinating or non-coordinating anion) as hydroformylation catalysts does not seem feasible.

Die doel van hierdie studie was die sintese van Ag(I) komplekse van die tipe [AgXLn] (L = tersiêre fosfien; n = 1-4; X = koördinerende of nie-koördinerende anioon) en verkenning van die olefien hidroformileringsaktiwiteit en liganduitruilings-tempo’s van hierdie komplekse. Tersiêre fosfien komplekse van Ag(I) van die tipe [AgXLn] (L = P(p-tol)3; n = 1-4; X = Br-, ClO4 -, PF6 -) is gesintetiseer en gekarakteriseer deur X-straal kristallografie. Gekose kristaldata word in Tabel 1 aangedui. Tabel 1 Gekose kristaldata soos verkry vir die drie Ag(I) kristalstukture bespreek in hierdie studie. Kompleks identifikasie [Ag{P(p-tol)3}4]PF6 [Ag{P(p-tol)3}3]ClO4 ·CH3COCH3 [Ag4{P(p-tol)3}4Br4] ·CH3COCH3 Ruimtegroep P213 (198) Pna21 (33) R 3 (148) Kristalstelsel Kubies Ortorombies Trigonaal (Ag-P)maks (Å) 2.6142 (7) 2.485 (1) 2.408 (2) (Ag-P)min (Å) 2.567 (1) 2.461 (1) 2.400 (1) Maksimum effektiewe keël hoek (°) 148.4 167.6 161.8 Hierdie komplekse is vergelykbaar met soortgelyke komplekse wat oorgangsmetale, ander fosfien ligande of verskillende teenione bevat. Die voorkoms van soortgelyke strukture in literatuur is egter beperk, wat `n gunstige area vir verdere studie aandui. Die gedrag van Ag/PX3 komplekse in oplossing is nog nie verken nie, as gevolg van, onder andere, vinnige en ingewikkelde kinetika, en kan uitgebrei word in die toekoms. Die koördinasie van hierdie komplekse met CO, vir toepassing as hidroformileringskataliste, is ondersoek deur middel van hoëdruk infrarooi spektroskopie. Geen bewyse van koördinering van CO met Ag(I) komplekse kon egter deur hoëdruk infrarooi spektroskopie gevind word nie. Die antipatie van die silwer molekule om die CO molekule te koördineer kan toegeskryf word aan die koördinasie van lywige fosfien ligande, wat die koördinasie van CO ligande aan die metaal senter kan verhoed, asook die afwesigheid van ’n sterk elektron-ontvangende ligand, byvoorbeeld boor- of stikstofbevattende ligande. Nog `n verduideliking is die hoë elektrondigtheid wat die silwer atom omring en -terugbinding van die silwer atoom na die CO molekule verhoed. Kinetika van die tempo van uitruiling tussen gekoördineerde fosfiene in die kompleks en vry fosfien is belangrik, aangesien hierdie uitruilingstempo moontlik `n invloed kan hê op die koördinering van die silwer atoom met ander ligande. Die uitruilingstempo is ondersoek deur middel van `n KMR tegniek genaamd magnetiese spin oordrag, of spin versadigingsoordrag. Met hierdie metode word die monster by `n spesifieke frekwensie versadig, en deur die ontspanning van die piek by daardie frekwensie kan die uitruiling tussen vry en gekoördineerde fosfien bestudeer word. Verskillende konsentrasies van die monster is ondersoek, wat saam met die berekende waardes van die tempo van uitruiling in Tabel 2 verskyn. Tabel 2 Berekende waardes vir kobs en T1 [PPh3]Totaal (mM) [PPh3]Vry (mM) [AgPF6] (mM) kobs (s-1) a) (kobs) (s-1) T1,Vry (s) a) T1, Koörd (s) 19.97 10.00 5.01 17.81 8.92 3.16 0.5411 0.4270 0.4624 7.167 7.609 6.640 1.595 1.444 1.341 8.285 4.808 4.049 0.5867 0.8704 0.6332 a) Geen geskatte standaardafwykings is verkry uit die berekeningsprogram nie, maar word geskat as ca. 10%. Die tempo van uitruiling vir die verskillende konsentrasies word aangedui in Figuur 1.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2007
Keywords: Silver compounds.; Alkenes; Transition metal complexes; Catalysts; CO coordination; Kinetics; Ligand exchange; Magnetization transfer; X-ray; High-pressure infrared; Hydroformylation; Characterization; Phosphine; Silver